African Elephant Specialist Group/Group des Specialistes des elephants d’Afrique - Dublin, Holly (Pachyderm, 2003)
Report reviews the ongoing collaborative work of the AfESG, accomplishments of the latter half of 2003 and challenges to be faced in the near future.